Two-photon energy distribution from the decay of the 2 1S0 state in He-like uranium - Banaś, Dariusz; Gumberidze, A.; Trotsenko, S.; Volotka, A. V.; Surzhykov, Andrey; Beyer, H. F.; Bosch, F.; Bräuning-Demian, A.; Fritzsche, S.; Hagmann, S.; Kozhuharov, C.; Kumar, A.; et al. (Physical review. A, Atomic, molecular, and optical physics, 2013)
We have performed a measurement of the spectral shape from the two-photon decay of the 1s2s1S0 state in He-like uranium. The two-photon emission followed the ionization of initially Li-like uranium ions in collisions with a N2 gas-jet target. The measured shape of the two-photon energy distribution shows good agreement with results of the relativistic calculations that take into account the electron-electron interaction rigorously up to the first order in quantum electrodynamic perturbation expansion. From the full width at half maximum of the measured two-photon energy distribution, we confirm the theoretically predicted modification of the shape due to the relativistic effects.